Incidence and recurrence of cutaneous leishmaniasis in a district of Piura, 2015-2023 - Solano, Fiorela E. (2025)
Objectives: To evaluate both incidence and recurrence associated factors for cutaneous leishmaniasis in Sapillica district, Piura, during the period 2015-2023, considering a description of the population and lesion characteristics, as well as to evaluate the risk for recurrence per year and its associated factors. Materials and methods: A single retrospective cohort study was performed using information available in databases of positive cases of cutaneous leishmaniasis between 2015 and 2023; cases from other districts were excluded. Excel 2019 was used for data cleaning, Qgis 3.34 incidence calculation for geospatial distribution according to affected communities, and STATA 15.0 for variable frequency, recurrence risk, and the evaluation of factors associated with recurrence with a 95% confidence level. Results: We found 280 patients with 406 lesions; 61.43% were male, median age was 24 years, and they were generally distributed in Llicsa Chica community. Nearly three quarters of patients (72.86%) presented a lesion; most of them were on the arms and were ulcerative. The absolute incidence was 31.11%, while the annual incidence reached more than 300 per 100,000 inhabitants. Conclusion: The incidence of cutaneous leishmaniasis increases in certain time periods; however, more years of follow-up are required to generalize these findings.